Efficient Simulations for Contamination of Groundwater Aquifers under Uncertainties. Issue 1 (18th November 2019) - Litvinenko, Alexander; Logashenko, Dmitry; Tempone, Raul; Wittum, Gabriel; Keyes, David
Abstract: Accurate modeling of contamination in subsurface flow and water aquifers is crucial for agriculture and environmental protection. Here, we demonstrate a parallel method to quantify the propagation of the uncertainty in the dispersal of pollution in density‐driven flow. We solve an Elder‐like problem, where we use random fields to model the limited knowledge on the porosity and permeability. The uncertain solution, mass fraction, is approximated via low‐cost generalized polynomial chaos expansion (gPCE). Parallelization is done in both the physical and parametric spaces.